Switzerland : Detailed Assessment of Observance-Insurance Core Principles. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This Detailed Assessment of Observance on the Insurance Core Principles on Switzerland analyzes that the insurance industry in Switzerland is well developed having among the highest insurance penetration and expenditure per capita in the world. The sector is dominated by a few players writing significant international business. The life sector is dominated by two players, responsible for 54 percent of the business and the top 10 life insurers account for 97 percent of the market. The industry has weathered the 2008 crisis well; however, the current low interest rate environment is affecting the sector. The lack of availability of Swiss government bonds to match long term liabilities of life insurers and pension funds could be a source of vulnerability. The long-term nature of the liabilities of life insurers and pension funds could in principle be matched by investment in Swiss government securities. Supervision focuses on ensuring sufficiency of liquid assets to meet policy liabilities. Policyholders have priority claims over the tied assets. In addition, robust solvency requirements ensure there is enough capital to safeguard the insurers' financial soundness under adverse conditions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet